The Effects of Head-and-Neck Temperature Manipulation and Motor Task Type on Central and Peripheral Fatigue, Motor Accuracy, and Stress-Related Blood Markers in Men With Multiple Sclerosis (Baltic Journal of Sport and Health Sciences, 2026)
Background and objectives: Multiple sclerosis (MS) is a chronic neurological disorder characterised by immune-mediated demyelination and axonal degeneration, leading to impaired motor control, fatigue, and reduced quality of life (Dobson & Giovannoni, 2019). Fatigue in MS arises from both central and peripheral mechanisms, with central fatigue linked to impaired neural drive and peripheral fatigue reflecting reduced muscle contractility (Tornero-Aguilera et al., 2022). Thermal stress further exacerbates fatigue in people with MS (PwMS), with heat impairing neural conduction and cooling, showing potential to improve performance and reduce exertion (Flensner et al., 2011; Grahn et al., 2008). The head and neck are highly thermosensitive regions, making them strategic sites for targeted thermal interventions (Desruelle & Candas, 2000). While cooling may enhance central motor drive and stress regulation via activation of cold-sensitive TRP channels (Gordon et al., 2020; Thapa et al., 2021), heating could worsen fatigue in thermally sensitive PwMS (Christogianni et al., 2018). Furthermore, motor task complexity – ranging from constant to unpredictable force demands – modulates central and peripheral fatigue expression (Kyguolienė et al., 2018; Taylor & Gandevia, 2008). However, the interactive effects of localised head-and-neck cooling or heating with different task complexities under thermoneutral conditions remain poorly understood. The dissertation aimed to address these gaps by investigating how localised thermal modulation influences central and peripheral fatigue, perceived exertion, and hormonal responses during submaximal isometric exercise in men with MS and healthy controls, providing novel insights for rehabilitation and fatigue management strategies.Methods: The dissertation comprised four randomised crossover studies with a minimum seven-day washout designed to evaluate the effects of localised head-and-neck cooling (18°C) and heating (44 ± 0.5°C) on central and peripheral fatigue during submaximal isometric knee-extensor exercise in men with relapsing-remitting multiple sclerosis (RRMS) and healthy controls. Ethical approval was obtained (BE-2-35), and the trial was registered (NCT06370403). Participants were men aged 18–45 years with RRMS or healthy controls.Studies I (COLD) and II (HEAT) were designed as separate investigations, each comparing localised head-and-neck cooling (18°C) or heating (44 ± 0.5°C) with a non-thermal control, to assess fatigue, neuromuscular performance, muscle contractility, and stress-related hormonal responses during 100 intermittent submaximal isometric contractions. Study III (COLD + TASKS) investigated how head-and-neck cooling interacts with motor task complexity (constant, predictable, unpredictable) to modulate neuromuscular responses, while Study IV (HEAT + TASKS) evaluated head-and-neck heating across the same task structures.Neuromuscular function was assessed via isokinetic dynamometry and surface EMG of the vastus lateralis, with outcomes including maximal voluntary contraction (MVC), central activation ratio (CAR), electrically evoked torque, contractile properties, and EMG root mean square (EMGrms). Muscle temperature was recorded intramuscularly, and venous blood samples were analysed for cortisol, prolactin, and dopamine. Perceived exertion was rated using the Borg scale, and motor accuracy was quantified via constant and absolute errors. Data were analysed using repeated-measures and mixed-design ANOVA with Bonferroni corrections, with significance set at p